Perception and attitude of tourists in Kerala scenario / Tony C Mathew and Sridevi N - Mathew, Tony C; N, Sridevi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Social media plays an important role in libraries today. Hence, this study aims to measure the level of social media capability in academic libraries. It aims to determine the significant impact of social media capability on librarians' agility and, in turn, the impact of librarian agility on relationship quality. Lastly, it examines how library policy moderates the relationship betweeThe phrase "staycation" refers to a time when a person or family stays at home and engages in leisure activities close to where they live without needing immediate convenience. Choosing where to travel is both an existing and troublesome inquiry for everybody the individuals who like to travel. Each voyager is picking an objective since it has something to draw in individuals or explorers. In this investigation, the researcher inspects the commonality of the term staycation among individuals particularly after the Covid-19 pandemic which confine individuals to travel. The analyst has recognized the components adding to discernment and mentality of vacationers towards staycation. The factors used in the study are cost, time and duration, closeness of destination, rest and relaxation, infrastructure facilities,, climate conditions, This study will make a clear idea regarding staycation , perception, and attitude among tourists. Pilot study is conducted among 40 respondents through a convenient sampling method which, is used to find out the factors contributing to perception and attitude of tourists towards staycation. The samples of 200 people of Kerala were chosen for the purpose of our study. So, data will be collected through structured questionnaire. The sampling is collected by convenient sampling method. The examination is gathered by an advantageous inspecting strategy. Subsequently, from this investigation the analyst infers that while choosing a traveler objective or the sort of travel industry it will be totally relies on the people individual decision. n librarians' agility and relationship quality. The study adopted the survey methodology and involved 30 librarians working in Tun Abdul Razak Library. The findings suggest that the respondents have a high social media capability. Furthermore, social media capability significantly affects librarians' agility, and librarians' agility also has a significant impact on relationship quality. Another notable finding is library policy moderates the relationship between librarians' agility and relationship quality. The findings can be used by relevant authorities to further improve their social media capability to cultivate better relationship quality between librarians and clients.